Hearing performance as a predictor of postural recovery in cochlear implant users - Greters,Mario Edvin (2017)
Abstract Objective This study aimed to evaluate if hearing performance is a predictor of postural control in cochlear implant (CI) users at least six months after surgery. Methods Cross-sectional study including (CI) recipients with post-lingual deafness and controls who were divided into the following groups: nine CI users with good hearing performance (G+), five CI users with poor hearing performance (G−), and seven controls (CG). For each patient, computerized dynamic posturography (CDP) tests, a sensory organization test (SOT), and an adaptation test (ADT) were applied as dual task performance, with first test (FT) and re-test (RT) on the same day, including a 40–60 min interval between them to evaluate the short-term learning ability on postural recovery strategies. The results of the groups were compared. Results Comparing the dual task performance on CDP and the weighted average between all test conditions, the G+ group showed better performance on RT in SOT4, SOT5, SOT6, and CS, which was not observed for G− and CG. The G− group had significantly lower levels of short-term learning ability than the other two groups in SOT5 (p = 0.021), SOT6 (p = 0.025), and CS (p = 0.031). Conclusion The CI users with good hearing performance had a higher index of postural recovery when compared to CI users with poor hearing performance.